Understanding and optimising plyometric training - Flanagan, E. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Plyometrics are exercises involving rapid, powerful movements preceded by a preloading countermovement. The stretch shortening cycle (SSC) is the basis of plyometric exercises. The precise mechanisms that underpin any SSC activity may be determined by the demands of the criterion task. As a result the SSCs can be classified as slow or fast. Accordingly, different plyometric exercises or the manner in which exercises are performed may elicit different mechanisms of SSC action. Slow SSC plyometrics are useful to teach athletes appropriate jumping and landing techniques and to develop maximal jumping ability. Fast SSC plyometrics develop athlete`s ability to generate high power outputs and fast rates of force development.